2018
DOI: 10.1111/imj.13711
|View full text |Cite
|
Sign up to set email alerts
|

Primary antifungal prophylaxis: decrease of invasive fungal disease incidence and reduction of risk factors in haematological patients in a 5‐year retrospective study

Abstract: PAP is necessary and efficient to prevent IFD in haematological patients, and the real-life PAP strategy is reasonable. Different drugs can be chosen, and it is better to start PAP as soon as neutropenia begins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
(143 reference statements)
0
7
0
Order By: Relevance
“…When it comes to the PAP, triazoles are always popular. 7,15 In a previous study, the proportions of different PAP were 75.8% (triazoles), 13.1% (echinocandins), and 11.1% (AmB). 7 Due to the epidemiological shift toward mold infections worldwide, fluconazole has not been the preferred choice to prevent IFDs.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…When it comes to the PAP, triazoles are always popular. 7,15 In a previous study, the proportions of different PAP were 75.8% (triazoles), 13.1% (echinocandins), and 11.1% (AmB). 7 Due to the epidemiological shift toward mold infections worldwide, fluconazole has not been the preferred choice to prevent IFDs.…”
Section: Discussionmentioning
confidence: 91%
“…7,15 In a previous study, the proportions of different PAP were 75.8% (triazoles), 13.1% (echinocandins), and 11.1% (AmB). 7 Due to the epidemiological shift toward mold infections worldwide, fluconazole has not been the preferred choice to prevent IFDs. 14 Mold-active prophylaxis, including posaconazole, voriconazole, itraconazole, and others, has been listed in the recommendations 9,10 and has significantly reduced the incidence of IFDs.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In Australia, regional areas tend to have older populations of PWH. 39 Regional areas in Australia tend to have less availability of GP able to be accessed without direct patient cost, which may increase utilisation of EDs. There are also less GP able to prescribe ARV in regional areas, increasing the need for two prescribers for PWH.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is now standard to use posaconazole as a prophylactic antifungal agent in induction chemotherapy for AML. However, some retrospective studies have reported that posaconazole has no significantly different effect on breakthrough IFD and 100-day mortality compared to other drugs [10,11]. This study aimed to compare the efficacy of posaconazole and itraconazole in the prevention of IFD in patients receiving first induction chemotherapy in a realworld setting.…”
Section: Introductionmentioning
confidence: 99%